The Effect of Compensation and Job Satisfaction on Employee Performance - Asma Pratiwi (P3M STIEM BONGAYA, 2021)
Objectively, this study aims to test and analyze partially and simultaneously the effect of compensation and job satisfaction on employee performance at the Office of the Ministry of Religion, Makassar City. This study involved 52 respondents, namely employees of the Makassar City Ministry of Religion. The analytical tool used is multiple linear regression analysis using the SPSS program with several stages of testing such as validity, reliability, normality, heteroscedasticity, and autocorrelation tests. To answer the hypothesis proposed in this study, hypothesis testing is done using the R Square test, T-test, and F-test. This study found that partially and simultaneously, compensation and job satisfaction have a positive and significant effect on employee performance at the Office of the Ministry of Religious Affairs in Makassar City.